Spremljanje in vrednotenje regionalne politike v Sloveniji - Kavaš, Damjan (Georitem, 2009)
The publication "Monitoring and Evaluation of Regional Policy in Slovenia" was prepared on the basis of the Assessment of Instruments and Mechanisms of Regional Policy project intended for designing the systems for the mid-term and final evaluation of Slovenia's regional policy. The project has prepared the basis for monitoring and evaluating the regional policy: we treated the monitoring of the regional policy as an important element in the overall development process because it enables constant supervision of the implementation of the policy and the evaluation of the regional policy as a constant interactive process that enables deliberate planning of activities and their adaptation to changing conditions. We focused on the characteristics of monitoring and evaluation in Slovenia's regional policy and prepared evaluation models that Slovenia's regional policy should follow in the future. Designing the models we drew from the existing Slovenian and European formal-legal frameworks for establishing monitoring and evaluation system in the 2007-2013 financial perspective.